Pengaruh Profitabilitas, Leverage, Operating Capacity dan Corporate Governance terhadap Financial Distress Perusahaan Ritel di BEI Tahun 2011-2017 - Ridwan Maronrong; Iman Sofian Suriawinata; Septiliana Septiliana (Jurnal Manajemen, 2022)
This study aims to determine the effect of profitability, leverage, operating capacity and corporate governance on financial distress in retail companies on the Indonesia Stock Exchange. This study uses a quantitative approach associative research, which is measured using the OLS-Data Panel and Logistics method with Eviews 10. The population of this study are retail companies listed on the Indonesia Stock Exchange (IDX) from 2011 to 2017. The sample is determined based on purposive sampling method, with a total sample of 18 retail companies so that the total observations in this study were 126 observations. The data used in this research is secondary data. The data collection technique uses the documentation method through the official IDX website: www.idx.co.id and the websites of each company. Hypothesis testing using t-test. The results of the study prove that profitability has a significant negative effect on financial distress, while leverage, operating capacity and corporate governance have a significant positive effect on financial distress.